MODEL OF LIQUID BOILING IN THE ACTUAL POROUS STRUCTURE AT THE NEAR-CRITICAL AREA WITH FURTHER TRANSFER TO THE LIMIT STATE OF COATING - A. A. Genbach; K.K. Shokolakov; D.Y. Bondartsev (Academic Journal of Physical and Chemical Sciences, 2019)
modelling of capillary porous coatings and analogy of their processes could help reveal a mechanism of heat transfer during evaporation of liquids, and determine zones for occurrence and development of fatigue fractures in the activation centers of vapour nucleus, research the natural deposits (saline deposits, scales) and artificial porous coatings on metal barriers (bases) up to the limit state of materials. Coatings were made of the poor conductive mineral medium (quartz, granite, teschenite) with low porosity (3÷30%). Heat was supplied from flame of the rocket burner and electric current. Stability of heat transfer is ensured by excessive cooler at the joint action of capillaryand mass forces. Solution of the thermoelastic problem has led to connection between the heat flows that destroy heat stress and fracture energy and time of the heat supply, as well as size of the pulled coating particles. The areas for relaxation, micro and macro destructive processes were determined, which point out the causes for occurrence and development of fatigue fractures of the heat-and-power equipment at stress concentrator along with erosion processes and relation between the limit state of compression and tension and unit. The conducted research refers to the transition operational modes of boiler turbine equipment, as well as formation of the capillary porous cooling system.